Effect of Pressure, Post-Pressing Time, and Polymerization Cycle on the Degree of Conversion of Thermoactivated Acrylic Resin - Rafaella de S. Leão; Sandra L. D. de Moraes; Kátia A. da S. Aquino; Cristina P. Isolan; Bruno G. da S. Casado; Marcos A. J. R. Montes (International Journal of Dentistry)
Herein, the effect of different post-pressing times and pressure in two cycles of polymerization on the degree of conversion (DC) of thermally activated acrylic resin (TRRA) is analyzed to optimize the polymerization of this material. After post-pressing for 0, 6, or 12 h, polymerization was performed with or without a pressure of 60 psi (0.41 MPa) in a short (4 h) or a long (11 h) cycle, totaling 12 groups. To determine the DC, PMMA specimens were analyzed by Fourier transform infrared spectroscopy. The influence of each factor alone on the DC was studied by experimental planning. The statistical tests used were three-way ANOVA, t-test, Tukey’s test, and Levene’s test, with a margin of error of 5%. Two groups prepared with post-pressing times of 12 h had the lowest DC (p<0.001). Post-pressing times of 0 and 6 h did not yield statistically different results. Pressure increased the DC in only one group (long cycle +12 h, p=0.001). The short cycle resulted in a higher DC than the long cycle in 2 groups (with pressure +0 h, p=0.002; without pressure +6 h, p=0.015), while the long cycle yielded a statistically higher DC in only one group (with pressure +12 h, p<0.001). The polymerization showed satisfactory DC in all 12 groups. Small differences found among the specimens indicate that the pressure, post-pressing time, and polymerization cycles herein were not influential factors for the DC of PMMA.